Biomarkers detected in cord blood predict vaccine responses in young infants - Baloh, Carolyn H.; Venturi, Guglielmo M.; Fischer, Bernard M.; Sadder, Liane S.; Kim-Chang, Julie J.; Chan, Cliburn; De Paris, Kristina; Yin, Li; Aldrovandi, Grace M.; Goodenow, Maureen M.; Sleasman, John W. (Frontiers in Immunology, 2023)
Factors influencing the breadth and character of infant immune priming involves both innate and adaptive immunity. Individual vaccine antigens vary in the cells and cytokines that optimally maintain vaccine specific antibody-mediated protection. This study examines plasma bioprofiles in 82 term, healthy infants who received standard immunizations during the first year of life. Changes in plasma biomarkers levels associated with germinal center development, macrophage activation, and T cell differentiation were used to test the hypothesis that bioprofiles associated with B cell survival best predicts sustained vaccine titers at one year. Measurements were performed at birth, soon after the initial vaccine battery at 6 months, and prior to the 12-month vaccinations. Post vaccination antibody titers to Bordetella pertussis, tetanus toxoid, and conjugated Haemophilus influenzae type B (HiB) were outcome measures. Using a least absolute shrinkage and selection operator (lasso) regression model, cord blood plasma IL-2, IL-17A, IL-31, and soluble CD14 (sCD14) were positively associated with pertussis titers at 12 months, while plasma levels of APRIL, and IL-33 at birth were negatively associated. In contrast, cord blood levels of sCD14 and APRIL positively associated with sustained tetanus titers. Elevated percentages of cord blood switched memory B cells were positively association with 12-month HiB titers. BAFF levels were positively associated with pertussis and HiB titers at 6 and 12 months, respectively. Feeding method, race, and gender did not significantly correlate with vaccine response. Sustained B cell immunity is highly influenced by early life immune dynamics within the germinal centers beginning at birth. The findings indicate that optimizing immunization responses of young infants should target early events in immune development.